Integration by Popular Culture: Brigitte Bardot as a Transnational Icon and European Integration in the 1950s and 1960s - Sherwood, Dana Whitney (Université d'Ottawa / University of Ottawa, 2011)
This thesis explores the history of European integration in the 1950s and 1960s from a popular cultural perspective anchored to a central figure from the era, Brigitte Bardot, in order to demonstrate that the peoples of Western Europe were engaged in processes of Europeanization that helped legitimize economic and political unions. Yet, official EU policy’s privileging of one (outdated) mode for understanding culture has handicapped alternative interpretations of a common European cultural heritage, failing to embrace a shared popular culture. Bardot is a suitable icon through which to begin an exploration into the diversity and significance of an integrating postwar European popular culture because she was a microcosm of several broad, transnational trends in postwar Europe including the rise of mass mobility, a major shift in European fashions, new gender constructions, and the explicit politicization of popular culture. Her films, career, lifestyle, and representation(s) provide key axes from which one can pivot into interrelated areas of European culture and societies in this era—pop culture; consumer culture; youth culture; mobility culture; media culture; political culture; and gender relations—demonstrating a widely integrating European popular cultural sphere. Within this context, Bardot was representative of broad postwar societal changes, served as a mass diffusion tool in relating these changes to the people of Europe, and functioned as a driving force in creating new transnational popular cultural forms. In addition, Bardot is a figure useful in understanding the relationship between Europe and the United States, while also demonstrating that economics is not separate from culture and popular culture. The Treaty of Rome, ostensibly about economic integration, further enabled the many circulations apparent in Bardot's career—people, goods, information, and ideas—that were already taking place. Furthermore, popular culture was not irrelevant to, or separate from politics and it helps to explain how the escapism and narcissism of European popular consumer culture could generate a rebellious, but sophisticated political consciousness. Western Europe does indeed have a distinct history of shared popular culture, which should be a factor in discussions of ‘Europeanization’ and the legitimacy of the European Union. It is necessary to explore the roots of this shared popular culture so that it does one day form the basis of a longstanding shared popular culture and can become a recognized element supporting the legitimacy of identities in the European Union in more fluid, dynamic ways.
Keywords: popular culture; Brigitte Bardot; European integration; mobility; ideology; postwar film; fashion; consumer culture; travel; tourism; celebrity; Europeanization; youth culture